Climate and Developmental Plasticity: Interannual Variability in Grapevine Leaf Morphology. Issue 3 (29th January 2016) - Chitwood, Daniel H.; Rundell, Susan M.; Li, Darren Y.; Woodford, Quaneisha L.; Yu, Tommy T.; Lopez, Jose R.; Greenblatt, Daniel; Kang, Julie; Londo, Jason P.
Abstract : Changes in climate alter specific shape features of grapevine leaves, regardless of evolutionary or developmental context. Abstract: The shapes of leaves are dynamic, changing over evolutionary time between species, within a single plant producing different shaped leaves at successive nodes, during the development of a single leaf as it allometrically expands, and in response to the environment. Notably, strong correlations between the dissection and size of leaves with temperature and precipitation exist in both the paleorecord and extant populations. Yet, a morphometric model integrating evolutionary, developmental, and environmental effects on leaf shape is lacking. Here, we continue a morphometric analysis of >5, 500 leaves representing 270 grapevines of multiple Vitis species between two growing seasons. Leaves are paired one-to-one and vine-to-vine accounting for developmental context, between growing seasons. Linear discriminant analysis reveals shape features that specifically define growing season, regardless of species or developmental context. The shape feature, a more pronounced distal sinus, is associated with the colder, drier growing season, consistent with patterns observed in the paleorecord. We discuss the implications of such plasticity in a long-lived woody perennial, such as grapevine ( Vitis spp.), with respect to the evolution and functionality of plant morphology and changes in climate.